Modelling and mending students' misconceptions in translating algebra word problems using a belief revision system in TAPS - Aziz, Normaziah A.; Pain, Helen; Brna, Paul (1995)
Abstract: "The goal of this research is to illustrate the potential of belief revision in a tutoring system for a domain where contradictions arise when students commit errors. We show how a belief revision system which employs the notion of epistemic entrenchment in resolving a conflict can be useful in modelling students and for remediation. Our particular focus is on: i) the domain of translating simple relational algebra word problems to algebraic equations; ii) misconceptions related to the reversal error; iii) student being persistent in holding the misconceptions which are referred to as the student's entrenched beliefs. We illustrate such investigations in TAPS (Translating Algebraic Problems System). TAPS, a prototype computer-based tutoring system has a belief revision system embedded in it which assists it in modelling and mending a student's misconceptions. It also helps TAPS in making overall observations of the student's performance."
Keywords: Bionics and artificial intelligence; Education and training; Belief and doubt; Computer-assisted instruction; Concepts; Word problems (Mathematics)